Kindful: design como facilitador a prática de mindfulness em crianças com TDAH - Zambom, Ana Carolina (My University, 2019)
The central theme of this study is to facilitate and encourage, through design, the practice of mindfulness exercises in children with Attention Deficit Hyperactivity Disorder. The beginning of the project presents a study of all the variables of the disorder, and how they affect the child's life in several aspects, including the family environment, which will be the focus. Information on how the behavior of the child with ADHD is characterized and the main chal-lenges were collected through qualitative interviews with the families. Children's area experts related to the subject, such as psychiatry, psychology, psychotherapy and professional experts in mindfulness and yoga also participated in the project, providing information of great importance. Market research was conducted to know what already exists and later, to create products and services that can be offered to the public in question. The proposed project contemplates visual identity, products and service. The communication, in turn, covers printed and digital stationery materials, considering visual patterns defined by the visual identity manual (sic).
O tema central deste trabalho consiste em facilitar e incentivar, através do design, a prática de exercícios da técnica de mindfulness, em crianças com Transtorno de Déficit de Atenção e Hiperatividade. O início do projeto apresenta um estudo acerca de todas as variáveis do transtorno, e de como as mesmas afetam a vida da criança em vários aspectos, incluindo no ambiente familiar, que será o foco principal. Informações de como se caracteriza o comportamento da criança com TDAH e os principais desafios encontrados, foram coletadas através de entrevistas de caráter qualitativo com as famílias. Especialistas de áreas infantis relacionadas ao tema, como psiquiatria, psicologia, psicoterapia e profissionais especialistas em mindfulness e yoga também participaram do projeto, fornecendo informações de grande importância. Foram realizadas pesquisas de mercado, com o intuito de conhecer o que já existe e posteriormente, criar produtos e serviços que possam ser oferecidos ao público em questão. O projeto proposto contempla identidade visual, produtos e serviço. A comunicação, por sua vez, abrange materiais de papelaria impressa e digital, considerando padrões visuais definidos pelo manual de identidade visual (sic).
Keywords: Design; Distúrbio do déficit de atenção com hiperatividade